Bone cancer pain - B Carolina Hernandez-Porras; Ricardo Plancarte; Juan Miguel Jimenez Andrade; Dhanalakshmi Koyyalagunta (Indian Journal of Pain, 2021)
In 2012, the International Agency for Research on Cancer reported 14.1 million new cancer cases, 8.2 million cancer deaths, and 32.6 million people living with cancer. Cancer pain not only causes significant suffering but also contributes to a decreased quality of life, functional status, and greatly increases health-care costs. The bones are a common site for metastases, especially tumors involving breast, lung, prostate, and kidneys. This can lead to significant pain, pathological fractures, compression of the spinal cord, poor quality of life, and increased mortality. Pathophysiology of cancer-induced bone pain is complex and has neuropathic and nociceptive characteristics. The aim of the treatment of bone metastases is palliating painful symptoms and preventing progression of skeletal-related events. A multimodal approach including various cancer therapies, analgesic and adjuvant agents, and interventional modalities should be used. This review focuses on the pathophysiology of bone cancer pain and pharmacological and non-pharmacological modalities that reduce bone cancer pain.